Use of predictive model to describe sporicidal and cell viability efficacy of betel leaf (Piper betle L.) essential oil on Aspergillus flavus and Penicillium expansum and its antifungal activity in raw apple juice. (July 2017) - Basak, Suradeep; Guha, Proshanta
Abstract: The present study describes the effect of betel leaf ( Piper betle L.) essential oil (BLEO) on spore inactivation and cell viability of Aspergillus flavus and Penicillium expansum using predictive model and its antifungal activity in raw apple juice. Survival curve of the spores under minimum fungicidal concentration of BLEO was modelled by a modified Weibull model: log N = log N 0 − ( t / δ ) β . The forward and side-scatter parameters of flow cytometer suggested differences in size and complexity of spores. Propidium iodide was used as fluorescent stain to distinguish between viable and non-viable spores. Scanning electron microscopic images revealed morphological alterations of treated spores. The cell viability effect of BLEO on mycelial matrix of A. flavus and P. expansum was measured using tetrazolium salt MTT and the inhibition was fitted to dose-response curves. Mycelial biomass of a selected mould in raw apple juice treated with BLEO based microemulsion (BLEO-ME) having different concentration of BLEO was determined based on ergosterol content. BLEO-ME exhibited fungal growth inhibition in raw apple juice, which suggests potential of BLEO as antifungal agent in food system. Highlights: The modified Weibull model described spore inactivation under influence of BLEO. in vitro antifungal activity was established using MTT assay. Antifungal effect in real apple juice was estimated in terms of ergosterol content. BLEO is a promising natural preservative to inhibit food spoilage.